Long intergenic non-coding RNA 00152 promotes lung adenocarcinoma proliferation via interacting with EZH2 and repressing IL24 expression. Issue 1 (December 2017) - Chen, Qin-nan; Chen, Xin; Chen, Zhen-yao; Nie, Feng-qi; Wei, Chen-chen; Ma, Hong-wei; Wan, Li; Yan, Shuai; Ren, Sheng-nan; Wang, Zhao-xia
Abstract Background Numerous studies have shown that long non-coding RNAs (lncRNAs) behave as a novel class of transcript during multiple cancer processes, such as cell proliferation, apoptosis, migration, and invasion. LINC00152 is located on chromosome 2p11.2, and has a transcript length of 828 nucleotides. The biological role of LINC00152 in LAD(lung adenocarcinoma) remains unknown. Methods Quantitative reverse transcription PCR(qRT-PCR) was used to detect LINC00152 expression in 60 human LAD tissues and paired normal tissues. In vitro and in vivo studies showed the biological function of LINC00152 in tumour progression. RNA transcriptome sequencing technology was performed to identify the downstream suppressor IL24(interleukin 24) which was further examined by qRT-PCR, western bolt and rescue experiments. RNA immunoprecipitation (RIP), RNA pulldown, and Chromatin immunoprecipitation (ChIP) assays were carried out to reveal the interaction between LINC00152, EZH2 and IL24. Results LINC00152 expression was upregulated in 60 human LAD tissues and paired normal tissues. High levels of LINC00152 expression were correlated with advanced TNM stage, larger tumor size, and lymph node metastasis, as well as shorter survival time. Silencing of LINC00152 suppressed cell growth and induced cell apoptosis. LINC00152 knockdown altered the expression of many downstream genes, including IL24. LINC00152 could interact with EZH2 and inhibit IL24 transcription. Moreover, the ectopic expression of IL24 repressed cell proliferation and partly reversed LINC00152 overexpression-induced promotion of cell growth in LAD. Conclusions Our study reveals an oncogenic role for LINC00152 in LAD tumorigenesis, suggesting that it could be used as a therapeutic target in LAD treatment.